2013
DOI: 10.1021/mp400358z
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Nanocurcumin to Attenuate Morphine Tolerance: Comparison between Negatively Charged PLGA and Partially and Fully PEGylated Nanoparticles

Abstract: We have formulated hydrophobic curcurmin [1,7-bis-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione] into stable nanoparticle suspensions (nano-curcumin) to overcome its relatively low bioavailability, high rate of metabolism and rapid elimination and clearance from the body. Employing the curcumin nanoformulations as the platform, we discovered that curcumin has the potential to alleviate morphine tolerance. The two types of stable polymeric nanoparticles - poly(lactic-co-glycolic acid) (PLGA) and poly(eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…PLGA-curcumin nanoparticles were generated by using a multi-inlet vortex mixer as previously described (Shen et al, 2013). One stream was 0.2% weight percent PLGA and 0.2% weight percent curcumin dissolved in tetrahydrofuran.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLGA-curcumin nanoparticles were generated by using a multi-inlet vortex mixer as previously described (Shen et al, 2013). One stream was 0.2% weight percent PLGA and 0.2% weight percent curcumin dissolved in tetrahydrofuran.…”
Section: Methodsmentioning
confidence: 99%
“…With the requirement of high doses in pharmacologic studies and poor solubility, it is difficult to independently confirm pharmacologic actions and ascertain the exact dose producing these effects. We have recently developed several polymeric nanoparticles encapsulating curcumin, including poly(lactic-coglycolic acid) (PLGA)-curcumin (Shen et al, 2013). In this study, we have more thoroughly characterized PLGA-curcumin in two rodent models of opioid tolerance and dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine, the most representative drug for the treatment of cancer pain, makes voltage-gated potassium channels of caudate nucleus neurons excited mainly through acting on μ receptor, which can inhibit voltage-gated calcium channel, make cytomembrane hyperpolarization and reduce the excitability of neurons which then cuts down the release of neurotransmitter of neuron axon endings, consequently blocking the transmission of nerve impulses and playing the role of nalgesic effect (Yang et al, 2014). The first pass effect of oral morphine is obvious, with low bioavailability (Shen et al, 2014). At present, there were 3 kinds of commonly-used opioids, belonging to long-acting formulations, such as morphine hydrochloride sustained-release tablets (morphine), sustained-release morphine (MS contin) and oxycodone hydrochloride controlled-release tablets (oxycodone).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a diarylheptanoid derived from turmeric, has generated immense interest as a lead compound against a variety of health conditions, including cancer, inflammation, microbial infection, angiogenesis, amyloidosis, wound healing, and alleviation of morphine tolerance. [70][71][72][73] However, poor bioavailability is a major limitation to the therapeutic utility of curcumin in clinical trials. 74 One animal study 75 found that when 1 g/kg of curcumin was orally administered, 75% of the compound was excreted through the feces.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…These data led the authors to conclude that the PLGA nanoparticles inhibit P-gp, which allows increased drug permeability and bioavailability. In a different study, Shen et al 73 compared the attenuation of morphine tolerance in mice induced by curcumin encapsulated in nanoparticles of PLGA and in nanoparticles of PEG-b-PLA. The mice that were given the curcumin-PLGA nanoparticles orally exhibited significantly greater attenuation of morphine tolerance than those mice given the curcumin-PEG-b-PLA nanoparticles, presumably due to greater absorption of the curcumin when formulated with PLGA.…”
mentioning
confidence: 99%